2010
DOI: 10.1007/s10764-010-9456-9
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Data on the Behavior, Ecology, and Morphology of Pygmy Tarsiers (Tarsius pumilus)

Abstract: We here present the first behavioral, morphological, and ecological data on a living group of highland pygmy tarsiers, Tarsius pumilus, and compare them with the lowland tarsier species of Sulawesi. Pygmy tarsiers were previously known only from 3 museum specimens and had not been seen alive since the first specimens were collected in 1917 and 1930. As part of a 2-mo exploratory study, we recently located a group consisting of ≥4 pygmy tarsiers in the mossy cloud forest of Lore Lindu National Park, Central Sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Unlike all other tarsier species, pygmy tarsiers are thought to be restricted to highland mossy cloud forest on the island of Sulawesi, Indonesia [Musser & Dagosto, ]. Previously, the species was known only from three museum specimens independently collected in the years 1917, 1930, and 2000 [Maryanto & Yani, ; Musser & Dagosto, ; Shekelle, ], until 2008 when we observed a live population in Lore Lindu National Park [Grow & Gursky‐Doyen, ]. Initial observations suggested pygmy tarsiers differ from the lowland Sulawesian tarsier species in terms of behavior (larger groups and cryptic communication strategies), morphology (an extremely small body size with a mean body mass of 55 g, and relatively long hindlimbs), and an apparently low population density [Grow & Gursky‐Doyen, ].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Unlike all other tarsier species, pygmy tarsiers are thought to be restricted to highland mossy cloud forest on the island of Sulawesi, Indonesia [Musser & Dagosto, ]. Previously, the species was known only from three museum specimens independently collected in the years 1917, 1930, and 2000 [Maryanto & Yani, ; Musser & Dagosto, ; Shekelle, ], until 2008 when we observed a live population in Lore Lindu National Park [Grow & Gursky‐Doyen, ]. Initial observations suggested pygmy tarsiers differ from the lowland Sulawesian tarsier species in terms of behavior (larger groups and cryptic communication strategies), morphology (an extremely small body size with a mean body mass of 55 g, and relatively long hindlimbs), and an apparently low population density [Grow & Gursky‐Doyen, ].…”
Section: Introductionmentioning
confidence: 91%
“…Previously, the species was known only from three museum specimens independently collected in the years 1917, 1930, and 2000 [Maryanto & Yani, ; Musser & Dagosto, ; Shekelle, ], until 2008 when we observed a live population in Lore Lindu National Park [Grow & Gursky‐Doyen, ]. Initial observations suggested pygmy tarsiers differ from the lowland Sulawesian tarsier species in terms of behavior (larger groups and cryptic communication strategies), morphology (an extremely small body size with a mean body mass of 55 g, and relatively long hindlimbs), and an apparently low population density [Grow & Gursky‐Doyen, ]. Some have hypothesized that these unusual traits are related to their high‐altitude habitat [Grow & Gursky‐Doyen, ; Musser & Dagosto, ].…”
Section: Introductionmentioning
confidence: 91%
“…They exhibit distinctive traits among tarsiers, including their anatomy (see Musser and Dagosto 1987) as well as cryptic behavior and communication (Grow and Gursky 2010). Until the first live observations of this species in 2008 (Grow and Gursky 2010), pygmy tarsiers were known only from three museum specimens, two of which were collected over 70 years ago: USNM 219454, found at 1,800 m at Rano Rano, AMNH 196477, found at 2,200 m at Latimojong, and MZB 22593, found at 2,200 m on Mt. Rore Katimbu (Maryanto and Yani 2004;Musser and Dagosto 1987).…”
Section: Study Speciesmentioning
confidence: 99%
“…Shekelle et al (1997, also in Shekelle 2003, 2008a reported results of field playback tests of Tarsius wallacei that unambiguously differentiated this species from T. dentatus, T. sangirensis, and as yet unnamed acoustic forms classified as T. tarsier, i.e., Manado, Gorontalo, Sejoli, and Togian forms. Indeed, differentiation of Tarsius wallacei from any known tarsier taxa other than the Togian form is trivial: 1) T. pumilus does not duet (Grow and Gursky-Doyen 2010;Shekelle 2008b).…”
Section: -T Dentatusmentioning
confidence: 99%